2021
DOI: 10.1186/s13148-021-01048-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential methylation EPIC analysis discloses cisplatin-resistance related hypermethylation and tumor-specific heterogeneity within matched primary and metastatic testicular germ cell tumor patient tissue samples

Abstract: Testicular germ cell tumors (TGCTs) are among the most common solid malignancies in young-adult men, and currently most mortality is due to metastatic disease and emergence of resistance to cisplatin. There is some evidence that increased methylation is one mechanism behind this resistance, stemming from individual studies, but approaches based on matched primary and metastatic patient samples are lacking. Herein, we provide an EPIC array-based study of matched primary and metastatic TGCT samples. Histology wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Recent studies suggest that global DNA hypermethylation may be a key factor in mediating cisplatin resistance in TGCTs [16,17]. The current work reveals that DNMT3B is also reciprocally altered with 5-aza and cisplatin resistance.…”
Section: Accepted Articlementioning
confidence: 53%
See 1 more Smart Citation
“…Recent studies suggest that global DNA hypermethylation may be a key factor in mediating cisplatin resistance in TGCTs [16,17]. The current work reveals that DNMT3B is also reciprocally altered with 5-aza and cisplatin resistance.…”
Section: Accepted Articlementioning
confidence: 53%
“…TGCT patients [17]. Our cisplatin resistant cells also possessed hypomethylation at polycomb target gene promoters, suggesting a complex crosstalk exists between the polycomb and DNA methylation pathways that influences cisplatin sensitivity of TGCT cells [16].…”
Section: Accepted Articlementioning
confidence: 77%
“…Hypermethylation of the CpG islands of the MLH1 promoter can lead to the accumulation of mismatched nucleotides and the generation of microsatellite instability [59] which have been linked to the poor prognosis of several tumour types but predominantly in colorectal cancers and endometrial cancers [60,61]. Epigenetic silencing of MLH1 is shown to be associated with aggressive tumours and cisplatin resistance in endometrial cancer [62,63] as well as in testicular germ cell tumours [64,65].…”
Section: Mismatch Repair Pathwaymentioning
confidence: 99%
“…Another concern that is also related to biomarkers is finding those that can predict response to more targeted (and possibly less toxic) therapies. The epigenetic landscape of TGCTs and its influence also on tumor aggressiveness and response/resistance to cisplatin treatment make epidrugs promising agents [4,13,[22][23][24][25]. In the result of epigenetic targeted therapy studies in TGCTs, other possible biomarkers have been identified, such as LSD1 [25][26][27].…”
Section: Introductionmentioning
confidence: 99%